Design of a non‐ferromagnetic spoke array Vernier permanent magnet generator with iron‐bar based on enhanced equivalent magnetic network model - Mehrage Ghods; Jawad Faiz; Ehsan Rashipour; Mohammad Amin Bazrafshan; Mohammad Reza Besmi (IET Electric Power Applications)
Abstract The spoke‐type arrangement of permanent magnets (PMs) in rotor of Vernier PM (VPM) machines was first introduced in a dual‐stator topology to overcome low‐power drawback of VPM machines. However, this structure is mostly applicable for high‐power motor drives. A non‐ferromagnetic spoke array VPM generator with a special rotor structure for small‐scale wind turbine generator is presented. The leakage flux lines tend to be aligned with the main flux routes due to a special design of flux barriers in end portion of PM housings. High torque‐density, low weight, torque‐speed curve with a wide constant torque region, promising efficiency, and power factor are the advantages of the proposed machine. An Equivalent‐Magnetic‐Network (EMN) model is established for predicting the complex behaviour of flux lines and operating quantities of the proposed structure with reasonable accuracy. The contribution of the modelling method includes a special mesh cell for the air‐gap permeance network to more accurately capture the flux routes, continuous positioning method for omitting spikes on post‐processing waveforms due to numerical errors, and a stable solving flowchart with a high convergence rate. The validity of the EMN model is validated by comparing the operating waveforms of the machine with the corresponding waveforms obtained by the finite element and experiments. The cover image is based on the Research Article Design of a non‐ferromagnetic spoke array Vernier permanent magnet generator with iron‐bar based on enhanced equivalent magnetic network model by Mehrage Ghods et al., https://doi.org/10.1049/elp2.12272.